2018
DOI: 10.1007/s00401-018-1837-8
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic astrocytoma with piloid features, a novel molecular class of IDH wildtype glioma with recurrent MAPK pathway, CDKN2A/B and ATRX alterations

Abstract: Tumors with histological features of pilocytic astrocytoma (PA), but with increased mitotic activity and additional high-grade features (particularly microvascular proliferation and palisading necrosis) have often been designated anaplastic pilocytic astrocytomas. The status of these tumors as a separate entity has not yet been conclusively demonstrated and molecular features have only been partially characterized. We performed DNA methylation profiling of 102 histologically defined anaplastic pilocytic astroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
213
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 221 publications
(232 citation statements)
references
References 55 publications
16
213
2
1
Order By: Relevance
“…Therefore, if the clinical, radiologic and histopathologic features are definitive for a diffusely infiltrative astrocytic glioma, TERT promoter mutations can be considered as a marker for WHO grade IV behavior. However, it should be emphasized that other types of IDH-wildtype glial neoplasms without WHO grade IV histology or aggressive behavior have also been reported to occasionally harbor TERT promoter mutations, including tumors classified as pleomorphic xanthoastrocytoma, ganglioglioma, anaplastic glioma with piloid features, and ependymoma [12, 25, 27, 31]. In addition, almost all oligodendrogliomas have TERT promoter mutations, and therefore this diagnostic consideration should be ruled out by testing for IDH mutations and 1p/19q codeletion.…”
Section: Recommended Grading Parameters: Egfr Amplification Combinedmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if the clinical, radiologic and histopathologic features are definitive for a diffusely infiltrative astrocytic glioma, TERT promoter mutations can be considered as a marker for WHO grade IV behavior. However, it should be emphasized that other types of IDH-wildtype glial neoplasms without WHO grade IV histology or aggressive behavior have also been reported to occasionally harbor TERT promoter mutations, including tumors classified as pleomorphic xanthoastrocytoma, ganglioglioma, anaplastic glioma with piloid features, and ependymoma [12, 25, 27, 31]. In addition, almost all oligodendrogliomas have TERT promoter mutations, and therefore this diagnostic consideration should be ruled out by testing for IDH mutations and 1p/19q codeletion.…”
Section: Recommended Grading Parameters: Egfr Amplification Combinedmentioning
confidence: 99%
“…Another subset of IDH-wildtype astrocytic gliomas has recently been delineated as anaplastic astrocytoma with piloid features, characterized by frequent CDKN2A/B deletions and typically accompanied by BRAF pathway gene alterations and ATRX mutation or loss of nuclear expression. The respective patients have a more favorable clinical outcome than patients with IDH-wildtype glioblastoma[25]. Therefore, by itself, CDKN2A/B deletion is not sufficient as a marker for WHO grade IV behavior in an IDH-wildtype astrocytic glioma.…”
Section: Other Possible Grading Parametersmentioning
confidence: 99%
“…A graphical summary of the evolution of the field within the context of brain tumours is displayed in Figure . DNA methylation is further gaining importance for tumour entity definition and is increasingly being used for the allocation of rare cancers into either known tumour classes or the identification of new entities , a collection of which are summarized in Figure .…”
Section: Dna Methylation In Cancermentioning
confidence: 99%
“…A recent, retrospective study by Reinhardt et al. of 102 cases, demonstrated that such tumors could reliably be identified by DNA methylation profiling, and that they often harbored deletions of CDKN2A/B , MAPK pathway gene alterations (most frequently NF1 , but also BRAF and FGFR1 ) and loss of ATRX expression (in 45% of the cases) . These patients were older than those with regular pilocytic astrocytomas (median age 41.5 years) and had a prognosis more in line with IDH ‐mutated glioblastomas.…”
Section: Low‐grade Pediatric Gliomas Mixed Glioneuronal Neoplasms Amentioning
confidence: 99%